2013
DOI: 10.1016/j.cyto.2013.06.312
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 prevents epithelial cell apoptosis by regulating IFNγ and TNFα expression in rhesus macaque colon explants

Abstract: Interleukin-10 (IL-10) is an important immunomodulatory cytokine that plays an obligate role in regulating inflammatory responses. Here we demonstrated the role of IL-10 in regulating crypts length and breadth as well as maintaining the survival of epithelial cells using rhesus colon explant cultures. Anti-IL-10 antibody treatment of colon explant cultures induced increased production of inflammatory cytokines/molecules like IFNγ, TNFα, CD107a and perforin as well as increased epithelial cell apoptosis compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…We have recently demonstrated the role of IL-10 in maintaining the survival of ECs and regulating crypt breadth using colon explant cultures (14). Our study suggested that IL-10 played an obligate role in maintaining mucosal homeostasis by regulating the production of mucosal gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣) cytokines.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…We have recently demonstrated the role of IL-10 in maintaining the survival of ECs and regulating crypt breadth using colon explant cultures (14). Our study suggested that IL-10 played an obligate role in maintaining mucosal homeostasis by regulating the production of mucosal gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣) cytokines.…”
mentioning
confidence: 88%
“…Colon specimens ϳ8 cm in length were collected in ice-cold Hanks balanced salt solution and were processed as described previously (14,25). Mucosal explants were treated with either anti-IL-10 monoclonal antibodies (MAbs; 5 g/ml; Biolegend), recombinant IL-10 (rIL-10) protein (50 ng/ml; Biolegend), or isotype control (5 g/ml; Biolegend) for 6 h as reported earlier (14).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations